Development of Hovercraft Landing Base/Platform at Seashore by Cementicious MF Polymer Sea-Sand Composites - U.C. Gupta, Satish; Pillai, V.N.; S. Gupta, Sandhya (Recent Innovations in Chemical Engineering, 2015)
For rapid construction of hovercraft landing platforms at sea shore various compositions of oxychloride cement (OCC) along with sea sand, melamine formaldehyde resin, guar gum and unsaturated polyester resins were prepared for optimization of the suitable composition with optimum compressive strength and elastic modulus. Based on results obtained further optimization was progressed. The Differential Scanning Calorimetric DSC and Thermo-gravimetric TG Analysis were recorded for Cross-linking Guar gum(CLGG), Melamine Formaldehyde (MF) Polymer, CLGG-MF polymer and CLGG-MF-OCC Composites to determine their thermal stability. Compressive strengths of the specimens prepared using CLGG-MF-OCC composite were determined by UTS machine and compared with other compositions. Polymeric concrete composite (PCC) made of aqueous solution of 2% CLGG-MF resin mixed with 25% magnesium oxychloride cement, 12% Fly ash and 60% Sea sand, was used to prepare platform on sea beach soil and it was found to have compressive strength up to 221.02 kg/cm2. Spraying grade CLGG-MF resin based composites were prepared for stabilization of soil by grouting and vulnerability of their sea sand composites towards encroaching water was studied. After curing, no cracks are developed on the surface. This composite is less expensive and ideally suited to make a rapid landing platform at sea shore and river banks which is not deteriorated by continuous slaps of encroaching water/rains as seen in Trials.
Keywords: Hovercraft Landing Platform